Butterfly Species Richness in Different Habitats of Pontianak City, West Kalimantan - Bibas, Elpe; Kurnia, Fitriyan; Raynaldo, Adityo; Marista, Etha; Wahyuni, Muftiah Yasi Dwi; Linda, Riza (Jurnal Biologi Tropis, 2025)
Urbanization drives biodiversity loss, but green spaces in Pontianak City may still serve as important refuges for butterflies. This study aims to assess butterfly species richness across different habitat types in Pontianak City, including agricultural, agroforestry, city parks, suburban areas, and marginal lands. Data were collected using the time-constrained counts method with a 30-minute observation period per site. Species richness was estimated using Chao1 estimator, diversity was analyzed with Hill numbers, and species composition was compared using the Chao-Sørensen similarity. A total of 438 individuals from 50 species were recorded. Agroforestry, suburban areas, and city parks exhibited relatively similar levels of species richness (28, 26, and 25 species, respectively), with agroforestry demonstrating the highest species richness and diversity (Shannon = 20, Simpson = 16). Conversely, agricultural areas (14 species) and marginal lands (7 species) showed comparatively lower species richness. The highest estimated species richness was found in city park habitats (36 species). Agricultural and marginal lands had the highest species similarity (0.77), whereas agroforestry and marginal lands had the lowest (0.22). These findings highlight agroforestry, suburban areas, and city parks as key conservation areas for butterflies. Habitat management strategies should prioritize these habitats to support butterfly diversity in Pontianak City.